KADAR OKSIGEN TERBAIK SEBAGAI DAYA TARIK WISATA KESEHATAN PADA PULAU GILI IYANG - Aryo Wibisono; Anik Anekawati; Suci Annisa (Fakultas Ekonomi dan Bisnis, 2021)
With so many coastal areas in Indonesia, it can provide a lot of potential that can be exploited such as the potential for fisheries, marine, agriculture, energy and tourism. One of the potentials that are in great demand by people is tourism. The potential for coastal tourism will have a beneficial impact on both the government and local communities living around the coastal areas if it can be managed properly. This study aims to determine the basis for determining Gili Iyang as a health tourism destination. To find out the role of the local village head in making Gili Iyang a health tourism destination. To find out the opinions of tourists who have visited Gili Iyang. To determine the role of oxygen levels in the human body. And the results of the research. From the results of this study, it can be concluded that the development of the island of Gili Iyang as tourists is still not fully able to run smoothly, because there are still several supports that need to be maximized. For example, there is a study on health on Gili Iyang Island so that later this island will be known for its health tourism. In addition, it would be better if you add several places to attract tourists visiting the island.